Macro Determinants of Export-Based MSMEs in Indonesia and Malaysia - M. Noor Salim; Nur Hayati Abd Rahman; Darwati Susilastuti; Pudji Astuty; Khairunnisa Abd Samad; Eri Marlapa (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
The primary objective of this study is to examine the key factors influencing the export performance of micro- and small-sector enterprises (MSMEs), aiming to identify critical elements that can enhance MSME growth and assess their implications for the Indonesian economy in comparison to Malaysia. The study aims to provide insights into the export of MSMEs, the simultaneous and partial effects of exchange rates, inflation, interest rates, GNI per capita, and labor on MSME exports in Indonesia and Malaysia, the identification of the most dominant factors among these variables affecting MSMEs exports for Indonesia, and a comparative analysis of MSME exported performance in both countries.